The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1176/appi.ajgp.12.5.531
|View full text |Cite
|
Sign up to set email alerts
|

Late-Life Depression Among Black and White Elderly Homecare Patients

Abstract: Objectives-The authors compared the prevalence of major depressive disorder (MDD) and the prescription rates of antidepressant medication, by race, among frail older homecare patients.Methods-A random sample of 56 black and 458 white newly admitted homecare patients age 65 and over were assessed for MDD with structured interviews and medical records, and antidepressant prescription rates were tallied.Results-The prevalence of MDD did not differ significantly across racial groups. Only 16.7% of black patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…RDC-defined MinD prevalence among older persons in hospice was reported as 9.2% (versus 16.9% for MDD); employing “Endicott criteria” (Endicott and Spitzer, 1979), which focus primarily on psychological depressive symptoms because neurovegetative symptoms among hospice patients are rampant, point prevalence was 12.3% for MinD and 10.3% for MDD (Chochinov et al, 1994). Three studies among older home healthcare recipients reported similar point prevalence of DSM-defined MinD (7.0, 8.2, and 10.8%) (Yewdell and Bennink, 1990; Fyffe et al, 2004). …”
Section: Resultsmentioning
confidence: 86%
“…RDC-defined MinD prevalence among older persons in hospice was reported as 9.2% (versus 16.9% for MDD); employing “Endicott criteria” (Endicott and Spitzer, 1979), which focus primarily on psychological depressive symptoms because neurovegetative symptoms among hospice patients are rampant, point prevalence was 12.3% for MinD and 10.3% for MDD (Chochinov et al, 1994). Three studies among older home healthcare recipients reported similar point prevalence of DSM-defined MinD (7.0, 8.2, and 10.8%) (Yewdell and Bennink, 1990; Fyffe et al, 2004). …”
Section: Resultsmentioning
confidence: 86%
“…These results can be viewed within two different contexts regarding the accuracy of the depression assessment. Studies of major depression in older homecare patients (Fyffe et al, 2004) and community dwelling adults (Byers et al, 2010;Jimenez et al, 2010) have shown no racial differences in prevalence of major depression. Therefore, one might also expect that the patients in this study had no significant differences in depression prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite overall increased rates of recognition of geriatric depression, disparities in depression care continue to exist for older homebound minority patients (Unützer et al, 2003;Bao et al, 2011). Although independent assessment of home healthcare (or homecare) patients demonstrated no racial differences in depression prevalence (Fyffe et al, 2004), national survey data of homecare agencies have shown lower rates of documented depression diagnosis and treatment with antidepressants in older African American homecare patients compared with that of the Caucasians (Weissman et al, 2011;Pickett et al, 2012). Rates of depression have been higher among older Hispanics with comorbid medical illness compared with those without physical complications, but the corresponding treatment rates remained low (Kemp et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…First, our analysis was based on an ethnically diverse sample in contrast to studies in which the patients were predominantly white. 54,55 Second, our study focused exclusively on patients over the age of 65 years in primary care settings. 56 Third, we were able to link the patient data to reports of physician identification of depression and somatization simultaneously within 6 months of interview.…”
Section: 48-53mentioning
confidence: 99%